PENINGKATAN KEMAMPUAN MENULIS SURAT LAMARAN PEKERJAAN MELALUI METODE TEAM GAME TOURNAMENT (TGT) PADA SISWA KELAS XII IS 3 SMA KRISTEN 1 SURAKARTA - Putro, Ely Prihmono Suwarso (Universitas Muhammadiyah Surakarta, 2007)
This research aimed at this class action research : (1) for description of stages;steps of applying of method TGT in course of study surat lamaran pekerjaan (2)for description the effectiveness of applying of method TGT to write surat lamaranpekerjaan of student of class of XII IS 3 SMA Kristen 1 Surakarta. Research procedurefollow the stages; steps of research of class action which relate of proposal ofResearch of Class Action (PTK) released by Dikti covering four step. Fourth stepof according to the Dikti (1) planning, (2) execution, (3) monitoring, and (4) refleksi.The outcome of the research was as follows: (1) effective method TGT enoughutilized in study write surat lamaran pekerjaan; (2) effective method TGT enoughto increase ability write surat lamaran pekerjaan; (3) effective to method TGTenough improve the student participation in study write surat lamaran pekerjaan;(4) effective to method TGT enough improve the motivation and student enthusiasmin study write surat lamaran pekerjaan.